Chemical and Fatty Acid Compositions of Date Palm Fruit (Phoenix dactylifera L) Flour (Bangladesh Journal of Scientific and Industrial Research, 2011)
The proximate, sugar, minerals and fatty acids composition of date palm fruit were determined. The moisture content is 5.24 ± 0.05%, ether extract value is 1.54 ± 0.01%, crude fibre content is 4.34+ 0.03%, crude protein content is 4.94+0.04% while the value of carbohydrate is 80.87 ± 0.05%. The fractions of sugar contained maltose (33.7mg%), fructose (22.8mg%) and glucose (22.3mg%). The most abundant minerals in the sample is potassium with the value of 710.0 mg% sample. The most concentrated fatty acids were oleic acid (44.51g/100g) > palmitic acid (23.05g/100g) > linoleic acid (11.66g/100g). All these quality food properties make it good source of unsaturated fatty acids and sweetening agent in food processing industry. Key words: Carbohydrates; Fatty acids; Minerals; Fruit flour. DOI: http://dx.doi.org/10.3329/bjsir.v46i2.8194 Bangladesh J. Sci. Ind. Res. 46(2), 255-258, 2011